Dissection of the Pre-Germinal Center B-Cell Maturation Pathway in Common Variable Immunodeficiency Based on Standardized Flow Cytometric EuroFlow Tools - del Pino-Molina, Lucía; López-Granados, Eduardo; Lecrevisse, Quentin; Torres Canizales, Juan; Pérez-Andrés, Martín; Blanco, Elena; Wentink, Marjolein; Bonroy, Carolien; Nechvatalova, Jana; Milota, Tomas; Kienzler, Anne-Kathrin; Philippé, Jan; et al. (Frontiers in Immunology, 2021)
CVID is characterized by defective antibody production and hypogammaglobulinemia. Flow cytometry immunophenotyping of blood lymphocytes has become of great relevance for the diagnosis and classification of CVID, due to an impaired differentiation of mature post-germinal-center (GC) class-switched memory B-cells (MBC) and severely decreased plasmablast/plasma cell (Pb) counts. We investigated in detail the pre-GC B-cell maturation compartment in blood of CVID patients. In this collaborative multicentric study the EuroFlow PID 8-color Pre-GC B-cell tube, standardized sample preparation procedures (SOPs) and innovative data analysis tools, were used to characterize the maturation profile of pre-GC B-cells in 100 CVID patients, vs 62 age-matched healthy donors (HD). The Pre-GC B-cell tube allowed identification within pre-GC B-cells of three subsets of maturation associated immature B-cells and three subpopulations of mature naïve B-lymphocytes. CVID patients showed overall reduced median absolute counts (vs HD) of the two more advanced stages of maturation of both CD5+ CD38+/++ CD21het CD24++ and CD5+ CD38het CD21+ CD24+ immature B cells (below normal HD levels in 22% and 37% of CVID patients). This was associated with an expansion of CD21-CD24- and CD21-CD24++ naïve B-cell counts above normal values in 73% and 94% cases, respectively. Additionally, reduced IgMD+ (21 vs 32 cells/uL, p=0.03) and IgMD- MBC counts were found to be below normal values in 25% and 77% of CVID patients, respectively, always together with severely reduced/undetectable circulating blood pb. Comparison of the maturation pathway profile of pre-GC B cells in blood of CVID patients vs HD using EuroFlow software tools showed systematically altered patterns in CVID. These consisted of: i) a normally-appearing maturation pathway with altered levels of expression of >1 (CD38, CD5, CD19, CD21, CD24 and/or smIgM) phenotypic marker (57/88 patients; 65%) for a total of 3 distinct CVID patient profiles and ii) CVID patients with a clearly altered pre-GC B cell maturation pathway in blood. Our results show that maturation of pre-GC B-cells in blood of CVID is systematically altered with up to four distinctly altered maturation profiles. Further studies, are necessary to better understand the impact of such alterations on the post-GC defects and the clinical heterogeneity of CVID.